2006
DOI: 10.1007/s00384-006-0144-3
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer in a population with endemic Schistosoma mansoni: is this an at-risk population?

Abstract: The data suggest that schistosomal colitis is more commonly associated with earlier onset of multicentric colorectal cancer, high percentage of mucinous adenocarcinoma, and presents at an advanced stage. The identification of a higher incidence of altered p53 expression in the SCC group raises the possibility of an association between schistosomiasis and alterations in p53 activation as an inciting event in colorectal cancer development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 23 publications
3
54
1
1
Order By: Relevance
“…In 1956, Dimmette et al (1956) failed to demonstrate any specific pathological changes in patients with simultaneous CRC and S. mansoni infestation, and considered the two conditions unrelated. Contrasting to these results, a recent study by Madbouly et al (2007) has shown that S. mansoni-associated colorectal cancer has distinctive pathological features often similar to those of colitis-induced carcinoma (Fig. 2a,b).…”
Section: Schistosoma Mansonicontrasting
confidence: 77%
See 2 more Smart Citations
“…In 1956, Dimmette et al (1956) failed to demonstrate any specific pathological changes in patients with simultaneous CRC and S. mansoni infestation, and considered the two conditions unrelated. Contrasting to these results, a recent study by Madbouly et al (2007) has shown that S. mansoni-associated colorectal cancer has distinctive pathological features often similar to those of colitis-induced carcinoma (Fig. 2a,b).…”
Section: Schistosoma Mansonicontrasting
confidence: 77%
“…In support of this view are data showing that CRC tends to occur mainly in patients who had history of schistosomiasis for 10 years or more and in whom the large bowel is wholly involved (Shindo, 1976;Ming-Chai et al, 1980). Moreover, there is significantly higher rate of synchronous tumours in patients with schistosomal colorectal cancer than in patients with spontaneous colorectal cancer (Ming-Chai et al, 1980;Madbouly et al, 2007). This can be ascribed to the field effect caused by chronic schistosomal inflammation throughout the colon, a phenomenon analogous to that described in the context of colitis-associated cancer.…”
Section: Mechanisms Of Tumorigenesismentioning
confidence: 89%
See 1 more Smart Citation
“…1 It has been well-documented that urinary bladder cancer is one of the major consequences of chronic infection with Schistosoma hematobium in many African and Middle East countries. 2 Among different species of Schistosoma inhibiting various countries and causing several diseases including cancers of the liver and colorectum, 3,4 the relationship between Schistosoma hematobium and urinary bladder cancer is the most important, and this organism has been classified by WHO/IARC as a Class 1 carcinogen. 5 When compared with their non-Schistosomal counterparts, Schistosoma-associated bladder carcinomas have 2 major clinicopathological features: the incidence reaches a peak in the 3rd-5th decades of life vs. the 7th decade in nonendemic areas, and there is significant increase in the ratios of squamous cell carcinomas (SCCs) to typical transitional urothelial carcinomas (UCs).…”
mentioning
confidence: 99%
“…Otra hipótesis que también podría explicar esta relación es el hecho de que el parásito habita en la mucosa donde libera sustancias que podrían inducir el desarrollo de neoplasias gastrointestinales 44,47 .…”
Section: Estrongiloidiasis Y Cáncer Gástricounclassified